2018
DOI: 10.1080/00223891.2018.1501568
|View full text |Cite
|
Sign up to set email alerts
|

Attorneys’ Attitudes Toward Coaching Forensic Clients on the MMPI–2: Replication and Extension of Attorney Survey by Wetter and Corrigan (1995)

Abstract: In this study we replicated and extended Wetter and Corrigan's ( 1995 ) commonly cited convenience survey of attorneys and law students regarding their attitudes toward coaching litigants prior to forensic psychological testing. We conducted a target survey of attorneys practicing in specialty areas of law where it is common to enlist psychological testing as part of legal proceedings (family law, juvenile law, personal injury, criminal law, social security/disability, workman's compensation). The estimated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Spengler et al (2018) replicated Wetter & Corrigan’s finding in a subsequent study and found that over 50% of attorneys endorse informing their clients specifically about Minnesota Multiphasic Personality Inventory validity scales. Spengler concludes that attorney coaching of test-taking examinees constitutes a serious threat to the validity of forensic psychological evaluations.…”
Section: Maintaining Test Security: Easier Said Than Donesupporting
confidence: 64%
See 2 more Smart Citations
“…Spengler et al (2018) replicated Wetter & Corrigan’s finding in a subsequent study and found that over 50% of attorneys endorse informing their clients specifically about Minnesota Multiphasic Personality Inventory validity scales. Spengler concludes that attorney coaching of test-taking examinees constitutes a serious threat to the validity of forensic psychological evaluations.…”
Section: Maintaining Test Security: Easier Said Than Donesupporting
confidence: 64%
“…Spengler et al (2018), for example, cites Frederick (2012), who has noted that, Whenever examiners reach a conclusion that psychopathology is present, and that the presence of psychopathology is relevant to some aspect of the case, the examiner should overtly address why and how malingering has been eliminated as an explanation. Many examiners fail to do so.…”
Section: Maintaining Test Security: Easier Said Than Donementioning
confidence: 99%
See 1 more Smart Citation
“…As information about psychological tests become increasingly accessible, it is important to identify non-genuine responders, even when they have been coached (or have coached themselves, using publicly available information) in how to evade detection. Moreover, research has demonstrated that defense attorneys often inform their clients about the validity scales embedded in psychological tests (Spengler et al, 2018; Wetter & Corrigan, 1995). Although the nature and quality of this coaching are largely unknown (e.g., the extent of attorney’s knowledge, the amount of time spent preparing their clients, the ability of clients to understand and utilize this information), it is certainly possible that justice-involved adults who are highly motivated to feign symptoms might perform better (i.e., generate lower validity scale scores, helping evade detection), particularly when compared to non-genuine participants in research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Information about psychological tests and psychiatric and medical symptomatology is easily accessible on the Internet, in textbooks, and in journals. Additionally, research has demonstrated that defense attorneys may feel compelled to warn, or even coach their clients on the disorder to be feigned and the detection strategies present in psychological measures (Lees-Haley, 1997; Rosen, 1995; Spengler et al, 2018; Wetter & Corrigan, 1995; Youngjohn, 1995). A national survey of 205 attorneys working in areas of the law in which psychological evaluations are frequent (i.e., criminal, juvenile, family, or personal injury law, social security/disability, workman’s compensation) found that most attorneys (73.2%, n = 150) supported providing general advice and information about psychological testing to their clients before a psychological evaluation (Spengler et al, 2018).…”
mentioning
confidence: 99%